Massive clot formation after tooth extraction - Santosh Hunasgi; Anila Koneru; Vardendra Manvikar; M Vanishree; R Surekha (Wolters Kluwer Medknow Publications, 2015)
Oral surgical procedures mainly tooth extraction can be related with an extended hemorrhage owed to the nature of the process resulting in an "open wound." The attempt of this paper is to present a case of massive postoperative clot formation after tooth extraction and highlight on the oral complications of surgical procedures. A 32-year-old male patient reported to the Dental Clinic for evaluation and extraction of grossly decayed 46. Clinical evaluation of 46 revealed root stumps. Extraction of the root stumps was performed, and it was uneventful. Hemostasis was achieved and postsurgical instructions were specified to the patient. The patient reported to the clinic, the very subsequent morning with a criticism of bleeding at the extraction site. On clinical examination, bleeding was noted from the socket in relation to 46. To control bleeding, oral hemostatic drugs Revici - E (Ethamsylate 500 mg) was prescribed and bleeding was stopped in 2 h. However, a massive clot was formed at the extraction site. Further, this clot resolved on its own in 1-week time. Despite the fact that dental extraction is considered to be a minor surgical procedure, some cases may present with life-threatening complications including hemorrhage. Vigilant and significant history taking, physical and dental examinations prior to dental procedures are a must to avoid intraoperative and postoperative complications.